2013
DOI: 10.1039/c2cp44013j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of chemical diffusion within secondary organic aerosol particles

Abstract: Formation, properties, transformations, and temporal evolution of secondary organic aerosol (SOA) particles depend strongly on SOA phase. Recent experimental evidence from both our group and several others indicates that, in contrast to common models' assumptions, SOA constituents do not form a low-viscosity, well-mixed solution, yielding instead a semisolid phase with high, but undetermined, viscosity. We find that when SOA particles are made in the presence of vapors of semi-volatile hydrophobic compounds, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
262
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 177 publications
(282 citation statements)
references
References 41 publications
(99 reference statements)
17
262
3
Order By: Relevance
“…At cool and/or dry conditions, however, we assume that highly viscous OA effectively shields BaP from heterogeneous oxidation, similar to that observed for eicosane (a highly viscous solid organic) coatings (18) (SI Appendix, Shielding of BaP by OA in the New Modeling Formulation). This approach is consistent with highly viscous SOA observed at dry conditions (27,28), persistence of highly viscous SOA at cooler temperatures in the free troposphere (26), and also higher viscosity of complex SOA mixtures (29) that are likely more atmospherically relevant compared with laboratory-generated SOA (SI Appendix, Shielding of BaP by OA in the New Modeling Formulation). We show that including the shielding of BaP by OA results in better agreement with BaP measurements in the field, promotes stronger long-range transport, and also produces greater global incremental lung cancer risk (ILCR) estimates due to exposure to PAHs, compared with the default model that neglects this shielding by OA.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…At cool and/or dry conditions, however, we assume that highly viscous OA effectively shields BaP from heterogeneous oxidation, similar to that observed for eicosane (a highly viscous solid organic) coatings (18) (SI Appendix, Shielding of BaP by OA in the New Modeling Formulation). This approach is consistent with highly viscous SOA observed at dry conditions (27,28), persistence of highly viscous SOA at cooler temperatures in the free troposphere (26), and also higher viscosity of complex SOA mixtures (29) that are likely more atmospherically relevant compared with laboratory-generated SOA (SI Appendix, Shielding of BaP by OA in the New Modeling Formulation). We show that including the shielding of BaP by OA results in better agreement with BaP measurements in the field, promotes stronger long-range transport, and also produces greater global incremental lung cancer risk (ILCR) estimates due to exposure to PAHs, compared with the default model that neglects this shielding by OA.…”
supporting
confidence: 61%
“…S4B). This result suggests that more complex and aged atmospheric SOA, which is highly viscous at cool/dry conditions (24,26,29), is expected to be highly effective in shielding BaP from oxidation, as is assumed in our new modeling formulation.…”
Section: Resultsmentioning
confidence: 76%
“…Namely (i) larger droplets can be studied allowing to better observe possible heterogeneities in the oxidised droplet composition and (ii) there is an opportunity for simultaneous measurement of more than one droplet under exactly the same experimental conditions and hence the possibility of better counting statistics. The latter advantage is depicted in Figure 4 where three droplets of different sizes (11,35 and 62 μm) are being imaged simultaneously while reacting with ozone. As seen in Figure 4B the total time required for all three droplets to reach at their maximum lifetime is 21 minutes, however individual droplets reach this maximum value at different times: 9 min for 11 μm droplet, 15 minutes for 35 μm droplet and 21 min for the largest 62 μm droplet.…”
Section: Resultsmentioning
confidence: 99%
“…An aerosol's viscous state also has direct implications on the particle morphology, phase behaviour, optical properties, aging processes and lifetime. At the same time, only few direct measurement methods are available for monitoring such properties 1, [6][7][8][9][10][11][12][13][14][15][16] . Recently, we have demonstrated that viscosity of model organic aerosols, such as oleic acid droplets, and secondary organic aerosols (SOA) produced from the oxidation of myrcene or -pinene can be measured and imaged in a spatially and time-resolved manner using Fluorescence Lifetime Imaging Microscopy (FLIM) of molecular rotors 17 .…”
Section: Introductionmentioning
confidence: 99%
“…This provides the basis for theoretical descriptions of secondary organic aerosols (SOA). However, recent studies of glass transition temperatures, 9 particle bouncing behaviour, 10 evaporation, [11][12][13] thermal desorption 14 and response to physical deformation 15 show that OM can adopt a semi-solid or amorphous solid (glassy) state under environmental conditions. Starting from aqueous organic liquids which exist in the atmosphere at high RH, the self-diffusion coefficient (of the organic solute) can decrease with decreasing RH from around 10 À8 cm 2 s À1 to less than 10 À20 cm 2 s…”
Section: Introductionmentioning
confidence: 99%